System to improve the starting characteristics of diesel engines at height - Lira Cacho, Guillermo (1999)
The theoretical foundations of a system to improve the starting of diesel engines at altitude are presented, which includes a special valve, called RND, used to introduce flammable liquids to the high pressure line of the injection system, and thus reduce the period ignition delay during startup. In addition, the partial cylinder disconnection method is proposed to prevent the engine from turning off after starting. Also, the experimental results of the starting time are presented, using flammable liquids, in a test bench with height simulation throttling the admission.